Futile care in COVID-19: how ICU nurses’ resilience impacts turnover intention? A cross-sectional descriptive study - Omid Zadi; Fatemeh Molaei Tavani; Mozhgan Behshid; Zahra Sheikhalipour; Parvin Rahmani; Mohammad Taghi KHodayari (BMC Health Services Research)
Abstract Background Futile care is a set of actions without creating a reasonable chance of benefiting critically ill patients. In the COVID-19 pandemic, there is a need to discuss futile care perception. This may cause unbearable pressure for nurses in terms of resilience and turnover intention.This study was designed to determine the ICU nurses’ perception of futile care in COVID-19 patients and its relationship with resilience and turnover intention. Methods This cross-sectional descriptive study was conducted on 251 nurses working in COVID-19 ICUs, in 2021 who were recruited with the quota sampling method. The data collection tools included questionnaires for demographic information, futile care, resilience assessment, and turnover intention. Collected data were analyzed using SPSS v26 software. Results A high mean level (64.78 ± 9.98) of futile care perception was found in the studied nurses, and their mean levels of turnover intention (36.4 ± 5.1) and resilience (65.5 ± 14.1) were evaluated at a moderate level. A significant and inverse relationship was observed between futile care perception and resilience (P = 0.047, rs = -0.077). There was a significant and positive relationship between futile care perception and turnover intention (P = 0.026, rs = 0.151). The resilience and turnover intention variables were correlated inversely and significantly (rs = -0.158, P = 0.014). Conclusion The adoption of appropriate strategies by managers can direct the nursing care path from futile to useful care. Given the significant relationship between resilience and turnover intention, it is recommended to teach strategies in the teaching program of nurses to enhance their resilience.